2013
DOI: 10.1371/journal.pone.0078102
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor TupA in Aspergillus niger Is Involved in Controlling Gene Expression Related to Cell Wall Biosynthesis, Development, and Nitrogen Source Availability

Abstract: The Tup1-Cyc8 (Ssn6) complex is a well characterized and conserved general transcriptional repressor complex in eukaryotic cells. Here, we report the identification of the Tup1 (TupA) homolog in the filamentous fungus Aspergillus niger in a genetic screen for mutants with a constitutive expression of the agsA gene. The agsA gene encodes a putative alpha-glucan synthase, which is induced in response to cell wall stress in A. niger. Apart from the constitutive expression of agsA, the selected mutant was also fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
2
15
0
Order By: Relevance
“…As pgxC is still partially repressed by glucose even in de creA mutant, an alternative repression mechanism might play a role. Although we could not link the TupA general repressor protein to glucose repression in A. niger (Schachtschabel et al, 2013), we cannot exclude a possible involvement of TupA in pgxC repression and this possibility will be addressed in future experiments. Finally, the promoter reporter strains in the DcreA background that still require an inducer for growth (pgaX, pgxB and pgxC) allow forward genetic screens for inducer-independent mutants.…”
Section: Discussionmentioning
confidence: 85%
“…As pgxC is still partially repressed by glucose even in de creA mutant, an alternative repression mechanism might play a role. Although we could not link the TupA general repressor protein to glucose repression in A. niger (Schachtschabel et al, 2013), we cannot exclude a possible involvement of TupA in pgxC repression and this possibility will be addressed in future experiments. Finally, the promoter reporter strains in the DcreA background that still require an inducer for growth (pgaX, pgxB and pgxC) allow forward genetic screens for inducer-independent mutants.…”
Section: Discussionmentioning
confidence: 85%
“…D). As Tup1 could regulate the expression of a series of cell wall biosynthesis‐associated genes in A. niger (Schachtschabel et al ., ), we examined the expression of these genes and found that they were down‐regulated in the Δ Motup1 mutant. The expression of the β‐1,3‐glucan synthase MoFKS1 (MGG_00865) (Fujikawa et al ., ) was also repressed in the Δ Motup1 mutant.…”
Section: Resultsmentioning
confidence: 91%
“…In addition to the genes found above, MoTup1 also regulates the expression of genes related to metabolism through the Tup1–Cyc8 complex (Keleher et al ., ; Schachtschabel et al ., ). We therefore examined the expression of the genes known to be involved in metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, deletion of two transcription factors important for securing cell wall integrity of A . niger (RlmA, [44]; TupA, [47] did also not affect anafp expression. Likewise, confrontation of A .…”
Section: Resultsmentioning
confidence: 99%